Comparison of Quality Physicochemical Longissimus Dorsi Mucsle of Ongole Crossbred Culled Cow Beef and Bali Culled Cow Beef - Fila Delfia; Gemini Ermiani Mereurina Malelak; Bastari Sabtu; Yakob Robert Noach (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2022)
Each meat of the breed has different quality of physicall and chemicall, they are several factors that influence it, one of them is age factor. The result of this research is to find the physical and chemical quality of the 6 years Ongole Crossbread culled cow beef and Bali culled cow beef from Longissimus dorsi sample. The treatments is T1 = Ongole Crossbreed culled cow beef and T2 = Bali culled cow beef with each treatments as much 4 cows as a replications. Data analysis in this research used t-Student test. Parameters observed were pH value, water holding capacity, cooking loss, moisture, protein, and fat content. Result of research indicated that have a significantly different (p<0.01) on pH value, water holding capacity, moisture, protein, and fat content. As well as cooking loss was not significantly different (p>0.05). Research that pH value, water holding capacity, and fat content Ongole Crossbreed Culled Cow Beef was higher than that of Bali Culled Cow Beef, but moisture and protein was lower than those of Bali Culled Cow Beef.